The sustainability mindset : using the matrix map to make strategic decisions - Zimmerman, Steve, 1970-; Bell, Jeanne, 1969- (San Francisco, CA : Jossey-Bass, 2014)
'The Matrix Map--a powerful tool for nonprofit strategic decision-makingNonprofit sustainability lies at the intersection of exceptional impact and financial viability. The Sustainability Mindset offers nonprofit professionals and board members a step-by-step guide to move your organization towards this intersection. As outlined in the bestselling book Nonprofit Sustainability,'The Matrix Map' is an accessible framework that combines financial and programmatic goals into an integrated strategy. In this next-step resource, the authors detail a rigorous process to develop a meaningful Matrix Map and engage leadership in setting an organization's strategy.Nonprofits that thrive in today's environment are adaptable with a clear understanding of their impact and business model. This book offers nonprofit boards and staff a framework to do so. Drawing on their in-depth experience, the authors provide an easy-to-follow process complete with tools and templates to help organizations visualize their business model and engage in strategic inquiry. The book provides a variety of illustrative examples to show how the Matrix Map works for all types of organizations. Nonprofit executives and board member are sure to benefit from The Matrix Map analysis. Offers step-by-step guidance for creating a Matrix-Map, a visual representation of an organization's business model Helps organizations assess how each of their programs contributes toward their desired impact and their financial bottom-line. Filled with compelling examples of how The Matrix Map helps nonprofits with strategic decision-making Written by the coauthors of the groundbreaking book Nonprofit Sustainability This comprehensive resource will give any nonprofit the framework they need to make decisions for sustainability and the templates and tools to implement it and help leaders address the challenges inherent in balancing mission impact with financial viability'--
'This book offers nonprofit professionals and board members a guide to implementing The Matrix Map-a proven model that is designed to give organizations the tools they need to sustain exceptional impact and long-term financial viability. The authors detail an accessible process that clearly shows how to incorporate the Matrix Map into an organization's strategic decision-making'--
Includes index.
Machine generated contents note: 1 Introduction 2 The Matrix Map 3 Getting Started: The Introductory Meeting 4 Articulating Impact 5 Assessing Mission Impact 6 Determining Profitability 7 Putting It All Together 8 Reading the Matrix Map: Developing the Key Messages 9 Program-Level Strategic Inquiry 10 Case Studies 11 The Sustainability Mindset Notes The Authors Index.
Keywords: Nonprofit organizations -- Finance; Nonprofit organizations -- Management